PENERAPAN PENDIDIKAN KESEHATAN TENTANG BUERGER ALLEN EXERCISE DENGAN METODE DRILL PADA PASIEN DIABETES MELLITUS - Nurjanah, Pina; Riyana, Asep; Bahtiar, Yanyan; Badriah, Siti (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2025)
There are 8,906 people with diabetes in Tasikmalaya City and 524 people in the Cilembang Health Center. The purpose of writing this scientific paper is to describe the characteristics of families with diabetes mellitus in the working area of the Cilembang Health Center, describe the results of assessing the ability of families to guide family members with diabetes mellitus in carrying out the buerger allen exercise, describe the implementation of health education about the buerger allen exercise using the drill method, describe the evaluation family ability to care for family members with diabetes mellitus after conducting health education about the buerger allen exercise using the drill method. Health education aims to increase one's knowledge. Buerger aillen exercise is an active activity in accelerating the joints so as to increase the ailment of the ailerons to the upper extremities. The design of this scientific paper is descriptive with a case study report by taking two cases in a family. Data collection techniques were carried out by interviews, observations, physical examinations, observation sheets and interviews as well as documentation studies. Case studies were carried out on April 6-13 2023 involving families. The nursing problem that arises is ineffective peripheral perfusion. The intervention strategy carried out was health education using the drill method about the buerger allen exercise. The evaluation results during the 5 day visit showed an increase in the ability of both families in guiding family members to carry out the buerger allen exercise. The conclusion is that there is a significant increase in both the knowledge, attitude and skill aspects. During the implementation of the family nursing case study, the author did not encounter significant obstacles because the family could work together, play an active role and also accept the explanations given. Scientific writing is expected to be a source of reference and foundation to support learning of family nursing care.